Conductive interface promoted bifunctional oxygen reduction/evolution activity in an ultra-low precious metal based hybrid catalyst - Sarkar, Shreya; Varghese, Merin; Vinod, C. P.; Peter, Sebastian C. (Chemical Communications, 2021)
Ultra low PtPd alloy deposited on Ni12P5 nanostructures (PtPd/Ni12P5) exhibited enhanced ORR activity (onset: 1.003 V and E-1/2:0.95 V) on par with commercial Pt/C and superior OER activity with 81% reduction of the precious metal compared to the commercial catalyst.